Assessment of microvessels density and inflammatory status in oral lichen planus - Ban F Al- Drobie (College of Dentistry/ University of Baghdad, 2014)
Background: Oral lichen planus (OLP) is a chronic inflammatory disease with an autoimmune inflammatory pathogenesis. The purpose of this study was to evaluate the role of angiogenesis in the pathogenesis of OLP, using CD34 stain to highlight the blood vessels for measuring the microvessel density (MVD) as well as to evaluate the relation of this marker with the degree of inflammation Materials and Methods: Immunohistochemical (IHC) staining technique was used to evaluate angiogenesis using CD34 in 46 paraffin blocks 10 of them obtained from normal mucosa and 36 from cases diagnosed as lichen planus , 20 of them diagnosed as Reticular type while 16 as erosive type. Severity of inflammation was divided into mild, moderate and severe according to the number of mononuclear cell infiltrate. Results: The mean MVD as determined by the mean number of CD34 positive vessels in hot areas for OLP group was higher 39.2 (31.9 for reticular group & 48.375 for erosive group), whereas the mean MVD for control group 19.5 so that there was statistically significant difference between OLP group and the control group (p value